Institutional Care in Four Latin American Countries: The Importance of Fostering Public Information and Evaluation Strategies; [Cuidados Institucionais Em Quatro Países Da América Latina: A Importância de Promover Informações Públicas E Estratégias de Avaliação]; [Atención en Centros de Cuidados a Largo Plazo en Cuatro Países de América Latina: Importancia de Fomentar la Información Pública y Las Estrategias de Evaluación] - Villalobos-Dintrans, P (Pan American Health Organization, 2024)
More than 8 million older people in Latin America depend on long-term care (LTC), accounting for 12% of people aged ≥ 60 years and almost 27% of those aged ≥ 80. It is crucial to develop sustainable strategies for providing LTC in the area, including institutional care. This special report aims to characterize institutional LTC in four countries (Brazil, Chile, Costa Rica and Mexico), using available information systems, and to identify the strategies adopted to support institutional care in these countries. This narrative review used nationwide, open-access, public data sources to gather demographic estimates and information about institutional LTC coverage and the availability of open-access data for the proportion of people with LTC needs, the number of LTC facilities and the number of residents living in them. These countries have a larger share of older people than the average in Latin America but fewer LTC facilities than required by the demand. National surveys lack standardization in defining disability, LTC and dependency on care. Information about institutional care is mainly fragmented and does not regularly include LTC facilities, their residents and workers. Data are crucial to inform evidence-based decisions to favor prioritization and to support advances in promoting policies around institutional LTC in Latin America. Although information about institutional care in the region is fragmented and insufficient, this paper profiles the four selected countries. It highlights the need for a better structure for data-driven LTC information systems. The lack of information emphasizes the urgency of the need to focus on and encourage research into this topic. © 2024 Pan American Health Organization. All rights reserved.
Keywords: Long-term care; aging; Latin America